2004
DOI: 10.1037/0012-1649.40.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Children who question their heterosexuality.

Abstract: Many gay, lesbian, and bisexual adults report a period of childhood sexual questioning--an uneasy questioning of their heterosexuality brought on by same-sex attractions and motivating same-sex sexual exploration. This article evaluates hypotheses about the correlates, causes, and consequences of childhood sexual questioning. Participants were 182 children in the 4th through 8th grades. Compared with children more confident in their heterosexuality, sexual-questioning children reported more impaired self-conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 33 publications
3
50
0
1
Order By: Relevance
“…At age 13, the children were administered the Multidimensional Gender Identity and Sexual Questioning Scale (Carver et al, 2004;Egan & Perry, 2001). This questionnaire was designed to assess adolescents' feelings of compatibility with their own gender and was specifically designed for this age group.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…At age 13, the children were administered the Multidimensional Gender Identity and Sexual Questioning Scale (Carver et al, 2004;Egan & Perry, 2001). This questionnaire was designed to assess adolescents' feelings of compatibility with their own gender and was specifically designed for this age group.…”
Section: Participantsmentioning
confidence: 99%
“…The Multidimensional Gender Identity Scale (Carver et al, 2004;Egan & Perry, 2001) was used to assess adolescents' sex-typed behavior. In the present investigation, the following (6) Female-typed activities-children's self-efficacy for female-typical activities, such as baby-sitting or looking after younger children [8 items].…”
Section: Multidimensional Gender Identity Scalementioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal research in which multidimensional models were used suggests how the kind of retrospective studies reviewed by Bailey and Zucker (1995) might be improved by stepping outside of the MF model. For example, Carver, Egan, and Perry (2004) found that children who question their heterosexuality engage in fewer same-sex activities than their peers, but they do not engage in a greater number of opposite-sex [page897] activities. Such children also come to see themselves as more atypically gendered as a consequence of questioning their heterosexuality.…”
Section: Rieger Et Al (2008): a Critiquementioning
confidence: 99%
“…Finally, the intervention does not posit an "essence" to MF but recognizes that gender nonconformity may persist or desist and may lead to gay/lesbian, bisexual, or straight adult identities (cf. Carver et al, 2004). In short, the intervention is interested in the child's well-being, understands familial bonds to be key to that well-being, and disattends to anxious questions about the child's eventual gender [page 898] identity or sexual identity on the basis of his or her current gender nonconformity.…”
Section: Drummond Et Al (2008): a Critiquementioning
confidence: 99%